Information and cognitive technologies in the life quality management through investments in the agricultural sector: synthesis and verification of system-cognitive models - T. P. Baranovskaya; E. V. Lutsenko (Новые технологии, 2018)
In previous studies the authors solved the problem of cognitive structurization and formalization of the subject area, which consisted in developing classification and descriptive scales and gradations and coding the source data with their help, as a result of which the training sample was formed. This paper is devoted to the synthesis and verification of a system-cognitive model, reflecting the impact of investments in the agro-industrial complex on the quality of life of the population of the region.